Analysis of Students’ Learning Outcomes Attention Deficit Hyperactivity Disorder in Indonesian Learning at Elementary School in Samarinda City - Hani Subakti; Eka Selvi Handayani; Nur Agus Salim; Kiftian Hady Prasetya; Hety Diana Septika (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aimed to determine the learning motivation of students with attention deficit hyperactivity disorder (ADHD) in Indonesian language learning for elementary schools. This research is descriptive qualitative using a purposive sampling technique with the subjects of students with attention deficit hyperactivity disorder (ADHD), class teachers, and parents. Data collection was performed through interviews and documentation to identify the learning motivation of students with attention deficit hyperactivity disorder (ADHD). The data were analyzed by data collection, data reduction, data presentation, and concluding. In testing the validity of the data, source triangulation was used. The results showed that students with attention deficit hyperactivity disorder (ADHD) had inattention, hyperactivity, and a combination-types accompanied by various symptoms showing the inability to focus attention. They looked different compared to other students of the same age. Those problems negatively influenced their cognitive, social, communication, and behavior development as well. In other words, the learning motivation of students with attention deficit hyperactivity disorder (ADHD) in Indonesian language learning was still relatively low. Parents and teachers should treat ADHD students with full affection and patience. Working together in educating and instilling good things is very significant to build motivation in learning the Indonesian language for elementary schools.